# Editing 2059: Modified Bayes' Theorem

**Warning:** You are not logged in. Your IP address will be publicly visible if you make any edits. If you **log in** or **create an account**, your edits will be attributed to your username, along with other benefits.

The edit can be undone.
Please check the comparison below to verify that this is what you want to do, and then save the changes below to finish undoing the edit.

Latest revision | Your text | ||

Line 32: | Line 32: | ||

==Transcript== | ==Transcript== | ||

− | + | {{incomplete transcript|Do NOT delete this tag too soon.}} | |

+ | |||

:Modified Bayes' theorem: | :Modified Bayes' theorem: | ||

− | |||

:P(H|X) = P(H) × (1 + P(C) × ( P(X|H)/P(X) - 1 )) | :P(H|X) = P(H) × (1 + P(C) × ( P(X|H)/P(X) - 1 )) | ||

− | |||

:H: Hypothesis | :H: Hypothesis | ||

:X: Observation | :X: Observation |